PENGARUH CITRA MEREK,PERSEPSI HARGA DAN CELEBRITY ENDORSEMENT TERHADAP KEPUTUSAN PEMBELIAN SUNSCREEN AZARINE DI KOTA SURABAYA - Muningka, Desy Nurpadillah; Maduwinarti, M.P, Dr. Dra. Ayun; Pratiwi, M.M, Dra. Ni Made Ida (Research Journal of Social Science and Economics, 2025)
Many new indigenous brands of skin care products have lately emerged in Indonesia, demonstrating the fierce competition now present in this market. The internet has made it possible for customers to share their product reviews and ratings with one another. Sunscreen is included among the skin care items since exposure to the sun may lead to skin darkening, the development of black spots, accelerated aging, and an overall uneven look of the skin. The purpose of this research is to identify how factors such as celebrity endorsement, perceived value, and brand image influence consumers’ decisions to buy Azarine sunscreen in the city of Surabaya. The data utilized is compiled using online survey responses from samples that meet the inclusion requirements, as well as data from the reference results. Data analysis with SPSS 25 software as an analytical tool and a Likert scale Surabaya, East Java, residents who have bought azarine sunscreens are utilized as a sample group. Purposive sampling was used in this study, and 100 people from the Sukolilo subdistrict of Surabaya city, East Java, who had recently bought Azarine sunscreen products made up the research sample. The methodology of this research is quantitative (multiple linear regression). Buying decisions for Azarine sunscreen in Surabaya were shown to be significantly influenced by consumers’ perceptions of the brand, the price, and a celebrity’s association with the product.